2017
DOI: 10.1186/s13034-017-0170-7
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in children and adolescents with bipolar I depression treated with olanzapine/fluoxetine combination

Abstract: BackgroundWe examined the efficacy of olanzapine/fluoxetine combination (OFC) in improving health-related quality of life (QoL) in the treatment of bipolar depression in children and adolescents.MethodsPatients aged 10–17 years with bipolar I disorder, depressed episode, baseline children’s depression rating scale-revised (CDRS-R) total score ≥40, Young Mania Rating Scale (YMRS) total score ≤15, and YMRS-item 1 ≤ 2 were randomized to OFC (6/25–12/50 mg/day olanzapine/fluoxetine; n = 170) or placebo (n = 85) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Similarly, Gonda and colleagues (2016) found that patients enhanced both their work functional outcome and QoL after receiving prophylactic lamotrigine therapy at 6-months follow-up. In young patients (10–17 years old) with an acute episode of bipolar depression, it was found that those who received olanzapine/fluoxetine combination presented better QoL scores compared with those receiving placebo (Walker et al, 2017).…”
Section: Personal Recovery: Well-being and Qolmentioning
confidence: 99%
“…Similarly, Gonda and colleagues (2016) found that patients enhanced both their work functional outcome and QoL after receiving prophylactic lamotrigine therapy at 6-months follow-up. In young patients (10–17 years old) with an acute episode of bipolar depression, it was found that those who received olanzapine/fluoxetine combination presented better QoL scores compared with those receiving placebo (Walker et al, 2017).…”
Section: Personal Recovery: Well-being and Qolmentioning
confidence: 99%
“…Among 34 studies, there were 28 numbers of unique PROMs identified. Thirteen measures were unique generic profile PROMs, among the most common were KIDSCREEN [ 29 , 43 , 44 , 48 , 51 ], Strengths and Difficulties Questionnaire (SDQ) [ 21 , 38 , 40 , 42 , 49 ], KINDL-R [ 45 47 ], [ 58 , 59 ], Pediatric Quality of Life Enjoyment and Satisfaction (PQ-LES-Q) [ 30 , 54 – 56 ], and the Pediatric Quality of Life Inventory (PedsQl) 4.0 [ 33 , 34 , 41 ]. There were two generic preference-based PROMs, the Euroqol (EQ-5D 3L and 5L), Health Utilities Index (HUI2/3) and thirteen measures were disease-specific, most of which were used in depression such as beck depression inventory (BDI) and child depression inventory (CDI) (Additional file 2 : S2).…”
Section: Resultsmentioning
confidence: 99%
“…Many of the PROMs in the included studies were administered to the child for self-report [ 27 33 , 35 , 38 , 40 , 44 , 48 50 , 52 , 54 – 58 ]. Twelve measures included both self-report and proxy report [ 21 , 28 , 29 , 41 47 , 51 , 58 ] and five measures have been reported by proxy only [ 34 , 36 , 37 , 41 , 44 ]. Proxy reporting was used in some studies due to a child’s young age and cognitive abilities (Additional file 2 : S2).…”
Section: Resultsmentioning
confidence: 99%
“…Fluoxetine is a serotonergic antidepressant which has been shown to lead to emotional stability across a broad spectrum of mental health conditions such as premenstrual emotional problems (92) , disruptive behaviour (93) , borderline personality disorder (94) and bipolar depression (95) . Therefore, it seems natural to use fluoxetine in people with bulimia nervosa, who suffer particularly from emotional dysregulation (96) .…”
Section: Advances In Drug Treatmentmentioning
confidence: 99%